Calcium lactate treatment of fresh-cut butternut squash (Cucurbita moschata): effect on texture during storage and shelf life - Mehlomakulu, Nwabisa (University of Pretoria, 2021)
Dissertation (MSc (Food Science))--University of Pretoria, 2020.